Acupuncture plus Rehabilitation for Unilateral Neglect after Stroke: A Systematic Review and Meta-Analysis. (10th March 2020) - Hou, Yonghui; Liu, Ying; Li, Minying; Ning, Baile; Wen, Zehuai; Fu, Wenbin
Abstract : Objectives . To systematically assess the efficacy of acupuncture combined with rehabilitation on unilateral neglect after stroke. Methods . The Cochrane Library, PubMed, Excerpt Medical Database (EMBASE), China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), Chinese Biomedical Literature Database (CBM), and Wan Fang databases were searched online for randomised controlled trials (RCTs) of acupuncture and its effects on unilateral neglect after stroke from their inception to September 2019. RCTs on acupuncture combined with rehabilitation in the experimental group for unilateral neglect compared with rehabilitation alone or rehabilitation plus sham acupuncture in the control group were included. Two authors separately screened the literature, extracted the data, and evaluated the quality of the included studies. Review Manager 5.3 software was used for the data analysis. Results . A total of 542 patients from nine RCTs were included. The meta-analysis showed that the experimental groups could significantly improve Fugl–Meyer Assessment (FMA) (MD = 11.54, 95% CI [9.54, 13.54], P < 0.00001 ) and the ability of daily living (SMD = 1.35, 95% CI [0.64, 2.07], P < 0.00001 ) when compared with the control groups. However, there was no significant difference in the drop of Catherine Bergego Scale (CBS) and Behavioural Inattention Test-conventional (BIT-C) between the two groups. Conclusions . Acupuncture combined with rehabilitation was more effective in improving the motor function and the ability of daily living. Because of the limitations regarding the quantity and quality of the studies in this meta-analysis, high-quality and well-designed RCTs are necessary to validate the above conclusions.